2006
DOI: 10.1111/j.1365-2095.2006.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diets for the tropical spiny lobster Panulirus ornatus: astaxanthin-supplemented feeds and mussel flesh

Abstract: The fast-growing tropical lobster Panulirus ornatus is a good aquaculture candidate generating increased research to develop potential feeds. We conducted a 12-week experiment, assessing growth, survival and tissue carotenoid levels of juvenile P. ornatus. Lobsters were fed either pelleted feeds supplemented with astaxanthin and containing 30, 60, 90 or 120 mg total carotenoid kg )1 ; or one of two fresh mussel reference feeds -blue Mytilus edulis and green-lipped Perna canaliculus. There was no clear dose res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 24 publications
(32 reference statements)
0
53
1
1
Order By: Relevance
“…Campbell (1969) showed that carotenoid content in blue mussels varies due to season of the year and maturity state of the mussels, but values of total carotenoid content in fresh mussels were never below 80 mg/kg (400 mg/kg DM). Barclay et al (2006) showed a similar carotenoid content of mussels (70 mg/kg, i.e. 280 mg/kg DM).…”
Section: Discussionmentioning
confidence: 69%
“…Campbell (1969) showed that carotenoid content in blue mussels varies due to season of the year and maturity state of the mussels, but values of total carotenoid content in fresh mussels were never below 80 mg/kg (400 mg/kg DM). Barclay et al (2006) showed a similar carotenoid content of mussels (70 mg/kg, i.e. 280 mg/kg DM).…”
Section: Discussionmentioning
confidence: 69%
“…Other carotenoid functions include conversion to retinoids that play a prominent role in prawn development and differentiation (Linan-Cabello et al, 2002). Increased levels of dietary carotenoid resulted in the accumulation of carotenoid esters in crustaceans (Yamada et al, 1990, Supamattaya et al, 2005, Boonyaratpalin et al, 2001, Barclay et al, 2006, Kumar et al, 2009, Wade et al, 2008. The esterification of carotenoids has been implicated in the regulation of pigmentation in several species (Wade et al, 2005, Wade et al, 2012, Tume et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Research effort over the past decades has considerably increased our knowledge about the nutritional requirements of spiny lobsters (Williams, 2007) but feeding most species with formulated diets on a least-cost basis is still a challenge. Spiny lobster growth performance is relatively poor when they are fed on dry formulated diets unless high levels of krill meal and/or krill hydrolysate are included (Smith et al, 2005;Barclay et al, 2006;Cox and Davis, 2009). It seems that spiny lobsters cannot efficiently use proteins from common aquafeed ingredients (e.g.…”
Section: Introductionmentioning
confidence: 99%